The Influence Of Hedonism Lifestyle, Consumptive Behavior And The Importance Of Financial Literacy On Personal Financial Management Of Sintang Students - Shagita Irbawiyanti; Yasir Hudzaifah; Romi Ferdian (UNIVED Press, 2025)
This research aims to find out how Sintang Regency students manage their personal finances related to the hedonism lifestyle, consumptive behavior and financial management. This research employs a quantitative methodology using a survey technique.The questionnaires were sent to collect the data 100 respondents who were Sintang Regency students, the data collected was then processed with tools by SPSS 27 data. The data are analyzed using multivariate linear regression. The results of this study show that financial literacy significantly and favorably affects Sintang Regency pupils, the Hedonism Lifestyle has a positive and significant impact on their financial management, and Consumptive Behavior has a negative and significant impact on their financial management.